Freud under the Muslim microscope: an analysis of his life and work - Abdul Razak, Mohd Abbas; Ali, Mohd Mumtaz (AbdulHamid A. AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences, IIUM, 2025)
Ever since time immemorial, man has been subjected to never-ending research. The curiosity to understand who man is has led researchers into many varied disciplines of knowledge. While philosophers and religious scholars sought to discover the purpose of man's existence on Earth, anthropologists were curious to solve the enigmatic question of the origin of man. Biologists, on their part, wanted to study the different systems at work in the human body. Finally, in the field of psychology, psychologists were interested in exploring how the mind works, particularly in areas such as learning, motivation, psy-chotherapy, personality development, creativity, and more. Though the psychological perspective on man has existed ever since the time of the Greek philosophers, the coming age of the European Enlightenment and Renaissance in the West injected new ideas to revamp the old ones. The Darwinian theory of human evolution took the masses in the opposite direction from what had been preached by the church and clergy. According to Darwin, Homo sapiens are no different from the rest of the animal kingdom. He further emphasised that the origin of man goes back to the ape family. By embrac-ing modern science and technology, a large section of the Eu-ropean community rejected ideas about man preached by sa-cred texts and church authority. With the introduction of Darwin's theory of evolution, Europe began to witness theories that shared similar views. One such theory, which emerged after Darwin, was conceptual-ized by Sigmund Freud. Drawing inspiration from Darwin and other sources, Freud developed a theory of human personality based on his observations of psychopathological patients who visited his clinic for psychotherapy. Having a strong back-ground in Jewish tradition and being acquainted with science and positivism, Freud eventually abandoned his old religious beliefs to formulate a theory of human nature that might seem profane or vulgar to those with religiously oriented thinking. According to Freud, the single most dominant energy that controls human activities is the libido, also called Eros. In simplifying things, he explained that all human activities and development, like personality, motivation, mental health, psy-chotherapy, creativity, etc., are based on the tussle that goes on among the id, ego and superego in the human psyche. Freud further elaborated that all human beings, regardless of where they are from, are shackled to the psychosexual development of the human psyche. Most simplistically, Freud viewed man as an intellectual beast doomed for destruction. Since Freud’s views on human nature are well-received in the West and are referenced in fields beyond psychology and psychotherapy, the researchers of this small-scale study would like to analyze his ideas on human nature and personality de-velopment from an Islamic perspective, particularly from the Islamic psychological viewpoint. The researchers assume that multiple factors may have influenced Freud’s thinking, leading him to adopt a deterministic and pessimistic view of human nature and personality development. In contrast to Freud’s views, Islam, as a religion, philosophy, and way of life, presents a positive image of humanity. The researchers have critically examined Freud’s ideas on human nature through analysis, evaluation, and an exploration from an Islamic perspective. In conclusion, the researchers would like to recommend this book to students and teachers of psychology, those in-volved in counselling and psychotherapy, religious scholars, and anyone interested in the ideas that Freud introduced to the world.